God's creativity and religious diversity: a theistic argument for a transformative pluralism. - Spica, Marciano Adilio (Religious Studies, 2025)
In this article, my objective is to argue for the compatibility between religious diversity and Christian theism by invoking the concept of divine creativity. I propose that, if God is a being of infinite powers and infinite creativity, He is such that it is possible for Him to create different and varied realities in a continuous process of creation. More than that, given His infinite creativity, God can reveal Himself in the most creative and diverse ways possible. There is no need for Him to reveal Himself as one and in a unique way, as some scholars of Christian theism argue. Basing my discussion on these ideas, I suggest that from the infinite creativity of God, it is possible to develop an argument in favour of a transformative pluralist view in face of religious diversity.